Simulation of the Performance of Kevlar Impregnated Shear Thickening Fluid Ballistic Test Results (STF) Ballistic Test Results - Prasetya, Riduwan; Andoko, Andoko; Suprayitno, Suprayitno; Wulandari, Retno; Trihutomo, Prihanto; Mishima, Kenji; Janas, Dawid (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
This study explores the enhancement of Kevlar fabric’s ballistic performance through impregnation with Shear Thickening Fluid (STF) for potential application in soft body armor. The experimental approach often fails to elucidate mechanical phenomena critical for the development of lightweight and high-strength body armor designs. To address this limitation, the finite element method, specifically using ANSYS/LS-DYNA R.13, was employed for a comprehensive analysis. The simulation aimed to evaluate the impact of STF on Kevlar fabric by assessing projectile velocity, force exerted by the projectile onto the fabric, displacement, stress distribution, and fabric failure mechanisms. Kevlar yarn was modeled as a shell element formed into fabric with a sine wave profile, investigating two types of STF: SiO2-PEG200 (S0) and SiO2-PEG200-B4C (S1), differing in maximum viscosities. The addition of STF resulted in increased coefficients of friction on Kevlar, with the highest values observed for the SiO2-PEG200-B4C impregnated fabric (  =0.87 and =0.82). The incorporation of the second STF type (S1) significantly reduced the projectile’s velocity from an initial 200 m/s to 153.2 m/s upon impact. Additionally, the force on the S1 fabric surged to 121,556 N, a threefold increase compared to neat Kevlar. STF's influence was further evidenced by enhanced fabric displacement and more uniform stress distribution upon ballistic impact. The fabric's thickening upon failure indicated STF's ability to enlarge the deformation area, facilitating uniform distribution of ballistic kinetic energy across the impact zone. Notably, the fabric impregnated with the second type of STF, featuring boron carbide (S1), demonstrated superior ballistic performance. This study concludes that STF-impregnated Kevlar fabric, particularly the SiO2-PEG200-B4C variant, not only surpasses the ballistic performance of neat Kevlar but also meets the criteria for NIJ Level IIIA standards, highlighting its potential as a highly effective material for advanced soft body armor designs.